2019
DOI: 10.3390/microorganisms7100457
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated Gene Replacement in the Fungal Keratitis Pathogen Fusarium solani var. petroliphilum

Abstract: Fungal keratitis (FK) is a site-threatening infection of the cornea associated with ocular trauma and contact lens wear. Members of the Fusarium solani species complex (FSSC) are predominant agents of FK worldwide, but genes that support their corneal virulence are poorly understood. As a means to bolster genetic analysis in FSSC pathogens, we sought to employ a CRISPR/Cas9 system in an FK isolate identified as Fusarium petroliphilum. Briefly, this approach involves the introduction of two components into fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The Fusarium petroliphilum strain used in this study is an FK isolate previously described ( Lightfoot and Fuller, 2019 ). To generate the inoculum, F. petroliphilum spores (microconidia) were inoculated into YPD broth and incubated for 2–3 days at 30 °C, shaking at 200 RPM.…”
Section: Methodsmentioning
confidence: 99%
“…The Fusarium petroliphilum strain used in this study is an FK isolate previously described ( Lightfoot and Fuller, 2019 ). To generate the inoculum, F. petroliphilum spores (microconidia) were inoculated into YPD broth and incubated for 2–3 days at 30 °C, shaking at 200 RPM.…”
Section: Methodsmentioning
confidence: 99%
“…Auxotrophic makers, such as amino acid auxotrophy, NADPH auxotrophy, thymidine auxotrophy and uracil auxotrophy, are useful tools in gene editing and vaccine products [21][22][23][24][25]. The uracil auxotrophy has been successfully constructed in multiple strains, and some uracil related genes, such as pyrF and ura3, are also widely used [23,[26][27][28]. Uracil nucleotides are indispensable in the process of bacterial life, and orotate is a key intermediate in the synthesis of uracil nucleotides.…”
Section: Baumanniimentioning
confidence: 99%
“…Researchers found that another type of non-antibiotic resistance selectable marker, i.e., auxotrophic markers such as amino acid auxotrophy, NADPH auxotrophy, thymidine auxotrophy, and uracil auxotrophy, is also a useful selectable tool in gene editing and vaccine production ( 17 21 ). Uracil auxotrophy has been successfully constructed in multiple strains, and some related genes are also widely used, such as pyrF , URA3, etc.…”
Section: Introductionmentioning
confidence: 99%